2012
DOI: 10.1371/journal.pone.0035999
|View full text |Cite
|
Sign up to set email alerts
|

Effects of PPARs Agonists on Cardiac Metabolism in Littermate and Cardiomyocyte-Specific PPAR-γ –Knockout (CM-PGKO) Mice

Abstract: Understanding the molecular regulatory mechanisms controlling for myocardial lipid metabolism is of critical importance for the development of new therapeutic strategies for heart diseases. The role of PPARγ and thiazolidinediones in regulation of myocardial lipid metabolism is controversial. The aim of our study was to assess the role of PPARγ on myocardial lipid metabolism and function and differentiate local/from systemic actions of PPARs agonists using cardiomyocyte-specific PPARγ –knockout (CM-PGKO) mice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 39 publications
0
16
1
Order By: Relevance
“…Fenofibrate increases the expression of fatty acid β‐oxidation enzymes in the fatty liver (Seo et al , ) and reduces SREBP1c expression (Barbieri et al , ). Both studies of AF indicated a significant down‐regulation of transcripts and proteins involved in lipid metabolism (Barth et al , ; Tu et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Fenofibrate increases the expression of fatty acid β‐oxidation enzymes in the fatty liver (Seo et al , ) and reduces SREBP1c expression (Barbieri et al , ). Both studies of AF indicated a significant down‐regulation of transcripts and proteins involved in lipid metabolism (Barth et al , ; Tu et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…In non-diabetic, non-obese humans and animal models, pioglitazone has repeatedly been demonstrated to increase CD36 mRNA or protein expression in multiple cell types including skeletal muscle [65], immune cells [66][67][68][69][70], endothelial cells [70], hepatic stellate cells [71], and adipose tissue [72]. A small number of studies have shown no increase in CD36 following pioglitazone in normal human adipose tissue [73], normal rat liver [74], and, interestingly, normal mouse cardiomyocytes [75]. It is currently unclear why the impact of pioglitazone on cardiomyocyte CD36 is different between our study and research carried out in mice [75].…”
Section: Can Target Engagement Of Pparγ By Pioglitazone Be Detected Imentioning
confidence: 99%
“…A small number of studies have shown no increase in CD36 following pioglitazone in normal human adipose tissue [73], normal rat liver [74], and, interestingly, normal mouse cardiomyocytes [75]. It is currently unclear why the impact of pioglitazone on cardiomyocyte CD36 is different between our study and research carried out in mice [75]. In addition to a possible species difference, it should be noted that the previous publication quantified CD36 mRNA level, in contrast to the current study, which investigated CD36 protein immunoreactivity and subcellular localization.…”
Section: Can Target Engagement Of Pparγ By Pioglitazone Be Detected Imentioning
confidence: 99%
“…Global PPAR γ −/− is lethal and the embryos have cardiac abnormalities caused by placental defects [ 126 ]. Cardiomyocyte-specific PPAR γ −/− mice develop cardiac hypertrophy with preserved systolic cardiac function and most likely have normal cardiac metabolism [ 127 129 ]. Increased NF κ B expression [ 127 ] or macrophage infiltration [ 128 ] might contribute to the development of hypertrophy.…”
Section: Ppar Animal Modelsmentioning
confidence: 99%
“…Lipid redistribution and decreased mitochondrial and ER stress might contribute to the improved cardiac function and survival. In cardiomyocyte PPAR δ −/− mice, treatment with the PPAR α agonist fenofibrate increased Cd36 and Cpt1 gene expression but did not affect myocardial lipid content [ 129 ].…”
Section: Ppar Animal Modelsmentioning
confidence: 99%